A Study of the Copyright Renewal Rate for Maps - Linda Musser (Issues in Science and Technology Librarianship)
This study examines the copyright renewal of maps published in the United States from 1923 to 1950 and compares the results with a recent study of copyright renewals for books. Results indicate that, while the average copyright renewal rate for maps appears similar to that of books, the average was skewed higher by a single publisher whose renewal rate was much higher than average. With the data from that publisher excluded, the average copyright renewal rate dropped to 10% meaning that a significant number of maps copyrighted in the U.S. in the first half of the 20th century are probably in the public domain due to lack of copyright renewal.